Effects of chitosan oligosaccharide on the growth performance, antioxidant capacity, immune function, intestinal digestive capacity and morphological structure in growing female minks - Hongfei Liu; Wenli Li; Gaoqiang Fan; Qiaoyi Chen; Shulei Zhang; Beibei Zhang (PLoS ONE, 2025)
This study aimed to investigate the effects of dietary chitosan oligosaccharide (COS) supplementation on growth performance, antioxidant capacity, immune function, duodenal digestive enzyme activity, and jejunal morphology in growing female minks. Ninety-six 12-week-old minks were randomly assigned to six groups (0, 100, 200, 300, 400, or 500 mg/kg COS), with 8 replicates per treatment and 2 minks per replicate, for an 8-week trial. The results showed that average daily gain (ADG) increased quadratically with increasing COS levels (P < 0.05) and 100 mg/kg COS significantly enhanced ADG (P < 0.05). Fresh pelt length increased linearly, and fresh pelt weight increased quadratically as COS levels increased (P < 0.05). COS supplementation significantly elevated serum immunoglobulin (Ig) A, IgG and complement 4 levels (P < 0.05). COS supplementation significantly increased serum superoxide dismutase activity and jejunal mucosal glutathione peroxidase activity, and significantly decreased serum malondialdehyde level (P < 0.05). Duodenal trypsin activity and the villus height-to-crypt depth ratio increased quadratically as COS levels increased (P < 0.05). In conclusion, dietary COS supplementation improved antioxidant capacity, immune function, duodenal digestive enzyme activity and jejunal morphology in growing female minks, thereby enhancing growth performance. The optimal dosage of COS is 100 mg/kg.